Expression of circular RNAs in myelodysplastic neoplasms and their association with mutations in the splicing factor gene SF3B1 - Trsova, Iva; Hrustincova, Andrea; Krejcik, Zdenek; Kundrat, David; Holoubek, Aleš; Staflova, Karolina; Janstova, Lucie; Vanikova, Sarka; Szikszai, Katarina; Klema, Jiri; Rysavy, Petr; Belickova, Monika; et al. (Molecular oncology, 2023)
Mutations in the splicing factor 3b subunit 1 (SF3B1) gene are frequent in myelodysplastic neoplasms (MDS). Because the splicing process is involved in the production of circular RNAs (circRNAs), we investigated the impact of SF3B1 mutations on circRNA processing. Using RNA sequencing, we measured circRNA expression in CD34+ bone marrow MDS cells. We defined circRNAs deregulated in a heterogeneous group of MDS patients and described increased circRNA formation in higher-risk MDS. We showed that the presence of SF3B1 mutations did not affect the global production of circRNAs; however, deregulation of specific circRNAs was observed. Particularly, we demonstrated that strong upregulation of circRNAs processed from the zinc finger E-box binding homeobox 1 (ZEB1) transcription factor; this upregulation was exclusive to SF3B1-mutated patients and was not observed in those with mutations in other splicing factors or other recurrently mutated genes, or with other clinical variables. Furthermore, we focused on the most upregulated ZEB1-circRNA, hsa_circ_0000228, and, by its knockdown, we demonstrated that its expression is related to mitochondrial activity. Using microRNA analyses, we proposed miR-1248 as a direct target of hsa_circ_0000228. To conclude, we demonstrated that mutated SF3B1 leads to deregulation of ZEB1-circRNAs, potentially contributing to the defects in mitochondrial metabolism observed in SF3B1-mutated MDS.
Keywords: fosfoproteiny; lidé; RNA, Circular; Transcription Factors; Leukemia, Myeloid, Acute; mutace; Humans; sestřihové faktory; Mutation; Myelodysplastic Syndromes; myelodysplastické syndromy; RNA Splicing Factors; transkripční faktory; akutní myeloidní leukemie; Phosphoproteins; kruhová RNA